The Influence of Technology and Social Media on Student Character Building - Sofie Raihana Tampubolon; Feby Aulia; Tari Lasmi Virginia Sihotang; Asmarianti Daulay; Gaby Sarah Giovani Sigalingging; Rido Pratama Ginting; Natalia Silalahi (PT. Global Research Collaboration, 2024)
The development of information technology can have a major impact in various aspects of life, including education. Technology can have a positive impact, such as easy access to teaching materials and online learning if used properly. However, inappropriate use of technology can have a negative impact on students' attitudes, ethics and character. This study aims to analyze the influence of technology and social media use on student character building using the literature review method. Based on the results of the research, it is found that technology and social media have a negative influence on students' morals, communication and responsibility, so in this case education has an important role to manage the negative impacts that arise with moral education, habituation and exemplary.